A large 'discovery' experiment: Gender Initiative for Excellence (Genie) at Chalmers University of Technology. (22nd June 2021) - Saline, Maria; Sheeran, Mary; Wittung-Stafshede, Pernilla
Abstract : Sweden tops gender equality rankings, but Swedish academia is still lacking women in top positions. To address gender inequality in its faculty, Chalmers University of Technology has invested 300 million SEK (30 million Euros) over 10 years in Gender initiative for Excellence (Genie). Genie aims to increase the university's success and excellence via gender equality efforts. In this editorial, we want to share insights on explicit efforts during Genie's first 2.5 years with the goal to inspire and advise other universities and researchers.